Study of the mechanisms of CO2 fixation in Ehrlich ascites tumor - Melgar Salmón, Ernesto (1962)
We conducted the study of the mechanisms of CO2 fixation in the Ehrlich ascites tumor , with the following results : 1. Ribose -5-phosphate was a slight stimulatory effect of fixing C14O2 ; however, could not be isolated 3- phosphoglyceric radioactive conditions that favored its accumulation . Two . Using pyruvic acid as a substrate , the amount of binding was higher . The addition of TPNH to said attachment homogenates greatly increased . Three . Isolates organic acids , the increased incorporation of C14 was detected in the succinic and malic . April . The partially purified acetone extracts showed activity of malic enzyme . The above results allow us to conclude that in the Ehrlich ascites tumor , CO2 fixation is performed almost exclusively by the action of malic enzyme , there being no evidence that it occurs at the level of ribulose -1 ,5- diphosphate.